Muhammad Abduh and Sufism: Building Spiritual Consciousness in the Context of Social Change - Ichwan, Moh. Nor; Mowafg Masuwd; Sya'roni, Mokh.; Abdulghani, Naser Ali (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
This article examines Muhammad Abduh's role in utilizing Sufism to build spiritual consciousness amid significant social changes in Egypt in the late 19th century. The main issue discussed was how Abduh combined the teachings of Sufism with social reform in the context of modernity, which is increasingly developing due to the influence of European colonialism and modernization pioneered by Muhammad Ali Pasha. This study explores how Abduh positioned Sufism as a moral tool supporting social reform. The method used is text analysis of Abduh's works and relevant secondary literature studies. The main findings show that Abduh has successfully integrated the spiritual dimension of Sufism with the demands of modernity, making Sufism a pillar to strengthen public morality and support harmonious social change. This article strongly recommends that further studies be conducted to understand how Abduh's approach to Sufism can be applied in contemporary social contexts that face similar challenges, as this could provide valuable insights for addressing current societal issues.